Selective synthesis of mono- and di-methylated amines using methanol and sodium azide as C1 and N1 sources. Issue 14 (28th June 2018) - Chakrabarti, Kaushik; Mishra, Anju; Panja, Dibyajyoti; Paul, Bhaskar; Kundu, Sabuj
Abstract : The selective synthesis of various N, N -dimethylated and N -monomethylated amines from organic azides using methanol as a methylating agent is reported. Abstract : A Ru(ii ) complex mediated synthesis of various N, N -dimethyl and N -monomethyl amines from organic azides using methanol as a methylating agent is reported. This methodology was successfully applied for a one-pot reaction of bromide derivatives and sodium azide in methanol. Notably, by controlling the reaction time several N -monomethylated and N, N -dimethylated amines were synthesized selectively. The practical applicability of this tandem process was revealed by preparative scale reactions with different organic azides and synthesis of an anti-vertigo drug betahistine. Several kinetic experiments and DFT studies were carried out to understand the mechanism of this transformation.